PENGARUH PEMBERDAYAAN, SIKAP KERJA, EFIKASI DIRI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR OTORITAS PELABUHAN UTAMA BELAWAN - Betty .; Julianto Sembiring; Muhammad Fadhlansyah Nasution; M. Syarizal Lubis; Tuahta Ginting (Universitas Islam Islam Sumatera Utara, 2021)
Problem of this study what is influence of empowerment on performance. What is influence of work attitude on performance. What is influence of self efficacy on performance. What is influence of organization culture on performance. What is influence empowerment, work attitude, self efficacy and organization culture on performance. The purpose of this study to determine and analyze the effect of empowerment on performance. Determine and analyze the effect of work attitude on performance. Determine and analyze the effect of self efficacy on performance. Determine and analyze the effect of organization culture on performance. Determine and analyze the effect of empowerment, work attitude, self efficacy and organization culture on performance. Sample in the study is 74 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate empowerment has a positive and significant effect on performance. Work attitude has a positive and significant effect on performance. Self efficacy has a positive and significant effect on performance. Organization culture has a positive and significant effect on performance. Empowerment, work attitude, self efficacy and organization culture has a positive and significant effect on performance.